ANALYSIS OF INDUSTRIAL FOREST PLANTS AS FITOREMEDIATION AGENTS OF HEAVY METALS FLY ASH CONTAMINATION - Fikri Daryat; Aslim Rasyad; Syafruddin Nasution (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2020)
Analysis of the ability of industrial forest plants such as A. crassicarpa and A. mangium can act as phytoremediation agents in absorbing heavy metals (Cd, Co and Pb) contained in coal-burning fly ash boilers that can be used as peat soil ameliorants. Provision of fly ash on peat soils has potential to pollute the soil. The purpose of this study was to analyze the effectiveness of forest indutrial plants in reducing heavy metal content in soils contaminated with fly ash and to estimate how much economic valuation is valued for the phytoremediation ability of acacia plants in the case of heavy metal contamination from pulp industry activities and paper.The results of the analysis of the ability of industrial forest plants in absorbing heavy metals show that A. crassicarpa is better at absorbing Pb metal, A. mangium is better at absorbing Co metals and Cd metal showed no significant difference between the two types of industrial forest plants.